Pengaruh Kegiatan Ekstrakurikuler terhadap Pembentukan Civic Dispostions Siswa SMK Negeri 1 Semendawai Timur - Fitri Untari Ningrum; Yunisca Nurmalisa; Rohman Rohman (FKIP Unila, 2018)
The purpose of this study was to determine the effect of extracurricular activities on the development of students' civic dispositions at East Semendawai Public Vocational High School 1 of South Sumatra Province academic year 2018/2019. This study applied descriptive quantitative method with students from grade X and XI participated in this study. The sample of the study consisted of 36 respondents. The data analysis was done by using Chi squares while the data collection techniques were done by questionnaires and also documentation as the supporting technique. The results of the study indicated that the extracurricular activities have influenced on the development of students' civic dispositions a rate of 0.71 has a significant (strong). Tujuan penelitian ini untuk mengetahui pengaruh kegiatan ekstrakurikuler terhadap pembentukan civic dispositions Siswa SMK Negeri 1 Semendawai Timur Provinsi Sumatera Selatan Tahun Ajaran 2018/2019. Metode penelitian yang digunakan metode deskriptif kuantitatif dengan subjek penelitian peserta didik kelas X dan XI. Sampel dalam penelitian ini berjuamlah 36 orang responden. Analisis data mengunakan Chi kuadrat dan tehnik pengumpulan data menggunakan angket dan tehnik penunjang adalah dokumentasi. Hasil penelitian ini menjukkan bahwa kegiatan esktrakurikuler sangat berpengaruh terhadap pembentukan civic dispositions pada angka 0,71 dikatagorikan kuat.Kata kunci: civic dispositions, ekstrakurikuler, kegiatan